2008
DOI: 10.1038/onc.2008.248
|View full text |Cite
|
Sign up to set email alerts
|

The role of PTEN signaling perturbations in cancer and in targeted therapy

Abstract: The PTEN tumor suppressor was discovered by its homozygous deletion and other mutations in cancer. Since then, PTEN has been shown to be a non-redundant, evolutionarily conserved phosphatase whose function affects diverse cellular progresses such as cell cycle progression, cell proliferation, chemotaxis, apoptosis, aging, muscle contractility, DNA damage response, angiogenesis and cell polarity. In accordance with its ability to influence multiple crucial cellular processes, PTEN has a major role in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
227
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(235 citation statements)
references
References 130 publications
(153 reference statements)
5
227
1
2
Order By: Relevance
“…PTEN encodes a lipid and protein phosphatase whose primary lipid substrate is PtdIns(3,4,5)P 3 . 2,[19][20][21][22] The purported protein substrate(s) of PTEN are more varied and controversial, including focal adhesion kinase, the Shc exchange protein and the transcriptional regulators ETS-2, CREB and Sp1 and the platelet-derived growth factor receptor as well as others. 23,24 PTEN has been recently shown to have nuclear activities and it may serve to dephosphorylate some transcription factors such as ETS-2, Sp1, CREB and others.…”
Section: Introductionmentioning
confidence: 99%
“…PTEN encodes a lipid and protein phosphatase whose primary lipid substrate is PtdIns(3,4,5)P 3 . 2,[19][20][21][22] The purported protein substrate(s) of PTEN are more varied and controversial, including focal adhesion kinase, the Shc exchange protein and the transcriptional regulators ETS-2, CREB and Sp1 and the platelet-derived growth factor receptor as well as others. 23,24 PTEN has been recently shown to have nuclear activities and it may serve to dephosphorylate some transcription factors such as ETS-2, Sp1, CREB and others.…”
Section: Introductionmentioning
confidence: 99%
“…Gain-of-function mutations in PIK3CA, the gene encoding the class I A PI3K catalytic subunit p110α, are frequently present in multiple human tumors (8). Second, the PIP3 phosphatase PTEN is a tumor suppressor frequently inactivated by mutation, gene deletion, and promoter methylation (9). Further, PI3K is potently activated by oncogenes like mutant Ras and tyrosine kinases such as Bcr-Abl, HER2 (ErbB2), MET, and KIT, among others (1).…”
mentioning
confidence: 99%
“…Therefore, AKT is activated by PI3K, which generates phosphatidylinositol 3, 4, 5-trisphosphate, and is negatively regulated by phospholipid phosphatases PTEN. 4 Hyperactivated AKT provides protection from apoptosis and promotes uncontrolled cell cycle progression. 5 However, it has recently been shown that AKT activity increases with cellular senescence, and that inhibition of AKT extends the lifespan of primary cultured human endothelial cells.…”
mentioning
confidence: 99%